# Review: Bananas, Lenses, Envelopes and Barbed Wire

Today’s classic functional programming paper we will review is Meijer et al.’s Functional Programming with Bananas, Lenses, Envelopes and Barbed Wire. The exciting gist of the paper is that all explicit recursion can be factored out into a few core combinators. As such, the reasoning is that we should instead learn these combinators (or “recursion schemes” as they’re called), rather than doing our own ad-hoc recursion whenever we need it.

Despite being a marvelous paper, it falls into the all-too-common flaw of functional programming papers, which is to have an absolutely horrible title. “Bananas”, “lenses”, “envelopes” and “barbed wire” correspond to obscure pieces of syntax invented to express these ideas. In our treatment of the literature, we will instead use standard Haskell syntax, and refer to the paper as Functional Programming with Recursion Schemes.

## Specialized Examples of Recursion Schemes

### Catamorphisms over Lists

**Catamorphisms** refer to a fold over a datastructure. A mnemonic to remember this is that a *cata*morphism tears down structures, and that if that structure were our civilization it’d be a *cata*strophe.

By way of example, Meijer et al. present the following specialization of a catamorphism over lists:

Let

`default :: b`

and`step :: a -> b -> b`

, then alist-catamorphism`h :: [a] -> b`

if a function of the following form:`= default h [] : as) = step a (h as) h (a`

This definition should look pretty familiar; if you specialize the function `foldr`

to lists, you’ll see it has the type:

`foldr :: (a -> b -> b) -> b -> [a] -> b`

We can view `foldr`

as taking our values `step :: a -> b -> b`

and `default :: b`

, and then giving back a function that takes an `[a]`

and computes some `b`

. For example, we can write a few of the common prelude functions over lists as catamorphisms of this form.

```
length :: [a] -> Int
length = foldr (\_ n -> n + 1) 0
```

```
filter :: forall a. (a -> Bool) -> [a] -> [a]
filter p = foldr step []
where
step :: a -> [a] -> [a]
= if p a
step a as then a : as
else as
```

When written this way – Meijer et al. are quick to point out – the so-called “fusion” law is easily seen:

```
. foldr step default = foldr step' default'
f where
= step a (f b)
step' a b = f default default'
```

which intuitively says that you can “fuse” a catamorphism with a subsequent composition into a single catamorphism.

### Anamorphisms over Lists

If a catamorphism refers to a “fold”, an **anamorphism** corresponds to an *unfold* of a data structure. A good mnemonic for this is that an *ana*morphism builds things up, just like *ana*bolic steroids can be an easy way to build up muscle mass.

Meijer et al. present this concept over lists with the following (again, very specialized) definition:

unfoldr :: (b -> Maybe (a, b)) -> b -> [a]

Given a function

`produce :: b -> Maybe (a, b)`

, a list-anamorphism`h :: b -> [a]`

is defined as:`= case produce seed of h seed Just (a, b) = a : h b Nothing = []`

As expected, this corresponds to the `unfoldr :: (b -> Maybe (a, b)) -> b -> [a]`

function from `Data.List`

.

By way of example, they provide the following:

```
zip :: ([a], [b]) -> [(a, b)]
zip = unfoldr produce
where
=
produce (as, bs) if null as || null bs
then Nothing
else Just ((head as, head bs), (tail as, tail bs))
```

and

```
iterate :: (a -> a) -> a -> [a]
iterate f = unfoldr (\a -> Just (a, f a))
```

An interesting case is that of `map :: (a -> b) -> [a] -> [b]`

. We note that both the input and output of this function are lists, and thus might suspect the function can be written as either a catamorphism *or* an anamorphism. And indeed, it can be:

```
cataMap :: (a -> b) -> [a] -> [b]
= foldr (\a bs -> f a : bs) []
cataMap f
anaMap :: (a -> b) -> [a] -> [b]
= unfoldr produce
anaMap f where
= Nothing
produce [] : as) = Just (f a, as) produce (a
```

Neat!

### Hylomorphisms over Lists

A **hylomorphism** over lists is a recursive function of type `a -> b`

whose call-tree is isomorphic to a list. A hylomorphism turns out to be nothing more than a catamorphism following an anamorphism; the anamorphism builds up the call-tree, and the catamorphism evaluates it.

An easy example of hylomorphisms is the factorial function, which can be naively (ie. without recursion schemes) implemented as follows:

```
fact :: Int -> Int
0 = 1
fact = n * fact (n - 1) fact n
```

When presented like this, it’s clear that `fact`

will be called a linear number of times in a tail-recursive fashion. That sounds a lot like a list to me, and indeed we can implement `fact`

as a hylomorphism:

```
fact :: Int -> Int
= foldr (*) 1 . unfoldr (\n -> if n == 0
fact then Nothing
else Just (n, n - 1))
```

The hylomorphic representation of `fact`

works by unfolding its argument `n`

into a list `[n, n-1 .. 1]`

, and then folding that list by multiplying every element in it.

However, as Meijer et al. point out, this implementation of `fact`

is a little unsatisfactory. Recall that the natural numbers are themselves an inductive type (`data Nat = Zero | Succ Nat`

), however, according to the paper, there is no easy catamorphism (nor anamorphism) that implements `fact`

.

### Paramorphisms

Enter **paramorphisms**: intuitively catamorphisms that have access to the current state of the structure-being-torn-down. Meijer et al.:

[Let

`init :: b`

and`merge :: Nat -> b -> b`

. ] For type`Nat`

, a paramorphism is a function`h :: Nat -> b`

of the form:`Zero = init h Succ n) = merge n (h n) h (`

As far as I can tell, there is no function in the Haskell standard library that corresponds to this function-as-specialized, so we will write it ourselves:

```
paraNat :: (Nat -> b -> b) -> b -> Nat -> b
init Zero = init
paraNat _ init (Succ n) = merge n (paraNat merge init n) paraNat merge
```

We can thus write `fact :: Nat -> Nat`

as a paramorphism:

```
fact :: Nat -> Nat
= paraNat (\n acc -> (1 + n) * acc) 1 fact
```

Similarly, we can define paramorphisms over lists via the function:

```
paraList :: (a -> [a] -> b -> b) -> b -> [a] -> b
init [] = init
paraList _ init (a : as) = merge a as (paraList merge init as) paraList merge
```

with which we can write the function `tails :: [a] -> [[a]]`

:

```
tails :: forall a. [a] -> [[a]]
= paraList merge []
tails where
merge :: a -> [a] -> [[a]] -> [[a]]
= (a : as) : ass merge a as ass
```

## General Recursion Schemes

### Intuition

As you’ve probably guessed, the reason we’ve been talking so much about these recursion schemes is that they generalize to all recursive data types. The trick, of course, is all in the representation.

Recall the standard definition of list:

```
data List a = Nil
| Cons a (List a)
```

However, there’s no reason we need the explicit recursion in the `Cons`

data structure. Consider instead, an alternative, “fixable” representation:

```
data List' a x = Nil'
| Cons' a x
```

If we were somehow able to convince the typesystem to unify `x ~ List' a x`

, we’d get the type `List' a (List' a (List' a ...))`

, which is obviously isomorphic to `List a`

. We’ll look at how to unify this in a second, but a more pressing question is “why would we want to express a list this way?”.

It’s a good question, and the answer is we’d want to do this because `List' a x`

is obviously a functor in `x`

. Furthermore, in general, any datastructure we perform this transformation on will be a functor in its previously-recursive `x`

parameter.

We’re left only more curious, however. What good is it to us if `List' a x`

is a functor in `x`

? It means that we can replace `x`

with some other type `b`

which is *not* isomorphic to `List a`

. If you squint and play a little loose with the type isomorphisms, this specializes `fmap :: (x -> b) -> List' a x -> List' a b`

to `(List a -> b) -> List' a x -> List' a b`

.

Notice the `List a -> b`

part of this function – that’s a fold of a `List a`

into a `b`

! Unfortunately we’re still left with a `List' a b`

, but this turns out to be a problem only in our handwaving of `x ~ List' a x`

, and the actual technique will in fact give us just a `b`

at the end of the day.

### Algebras

An `f`

-algebra is a function of type `forall z. f z -> z`

, which intuitively removes the structure of an `f`

. If you think about it, this is spiritually what a fold does; it removes some structure as it reduces to some value.

As it happens, the type of an `f`

-algebra is identical to the parameters required by a catamorphism. Let’s look at `List' a`

-algebras and see how the correspond with our previous examples of catamorphisms.

```
length :: [a] -> Int
length = foldr (\_ n -> n + 1) 0
lengthAlgebra :: List' a Int -> Int
Nil' = 0
lengthAlgebra Cons' _ n) = n + 1 lengthAlgebra (
```

```
filter :: forall a. (a -> Bool) -> List a -> List a
filter p = foldr step Nil
where
=
step a as if p a
then Cons a as
else as
filterAlgebra :: (a -> Bool) -> List' a (List a) -> (List a)
Nil' = Nil
filterAlgebra _ Cons' a as) =
filterAlgebra p (if p a
then Cons a as
else as
```

### Coalgebras

`f`

-algebras correspond succinctly to the parameters of catamorphisms over `f`

s. Since catamorphisms are dual to anamorphisms, we should expect that by turning around an algebra we might get a representation of the anamorphism parameters.

And we’d be right. Such a thing is called an `f`

-coalgebra of type `forall z. z -> f z`

, and corresponds exactly to these parameters. Let’s look at our previous examples of anamorphisms through this lens:

```
zip :: (List a, List b) -> List (a, b)
zip = unfoldr produce
where
=
produce (as, bs) if null as || null bs
then Nothing
else Just ((head as, head bs), (tail as, tail bs))
zipCoalgebra :: ([a], [b]) -> List' (a, b) ([a], [b])
=
zipCoalgebra (as, bs) if null as || null bs
then Nil'
else Cons (head as, head bs) (tail as, tail bs)
```

```
iterate :: (a -> a) -> a -> [a]
iterate f = unfoldr (\a -> Just (a, f a))
iterateAlgebra :: (a -> a) -> a -> List' a a
= Cons a (f a) iterateAlgebra f a
```

You might have noticed that these coalgebras don’t line up as nicely as the algebras did, due namely to the `produce`

functions returning a type of `Maybe (a, b)`

, while the coalgebras return a `List' a b`

. Of course, these types are isomorphic (`Nothing <=> Nil'`

, `Just (a, b) <=> Cons a b`

), it’s just that the authors of `unfoldr`

didn’t have our `List'`

functor to play with.

### From Algebras to Catamorphisms

As we have seen, `f`

-algebras correspond exactly to the parameters of a catamorphism over an `f`

. But how can we actually implement the catamorphism? We’re almost there, but first we need some machinery.

`type family Fixable t :: * -> *`

The type family `Fixable`

takes a type to its fixable functor representation. For example, we can use it to connect our `List a`

type to `List' a`

:

`type instance Fixable (List a) = List' a`

Now, assuming we have a function `toFixable :: t -> Fixable t t`

, which for lists looks like this:

```
toFixable :: List a -> Fixable (List a) (List a)
-- equivalently: toFixable :: List a -> List' a (List a)
Nil = Nil'
toFixable Cons a as) = Cons' a as toFixable (
```

We can now write our catamorphism!

```
cata :: (Fixable t z -> z) -> (t -> z)
= algebra
cata algebra . fmap (cata algebra)
. toFixable
```

Very cool. What we’ve built here is general machinery for tearing down any inductive data structure `t`

. All we need to do it is its `Fixable t`

representation, and a function `project :: t -> Fixable t t`

. These definitions turn out to be completely mechanical, and thankfully, can be automatically derived for you via the recursion-schemes package.

### Coalgebras and Catamorphisms

We can turn all of our machinery around in order to implement anamorphisms. We’ll present this material quickly without much commentary, since there are no new insights here.

Given `fromFixable :: Fixable t t -> t`

, we can implement `ana`

:

```
ana :: (z -> Fixable t z) -> z -> t
= fromFixable
ana coalgebra . fmap (ana coalgebra)
. coalgebra
```

### General Paramorphisms

Because there is nothing interesting about hylomorphisms when viewed via our `Fixable`

machinery, we skip directly to paramorphisms.

Recall that a paramorphism is a fold that has access to both the accumulated value being constructed as well as the remainder of the structure at any given point in time. We can represent such a thing “algebraically:” `Fixable t (t, z) -> z`

. With a minor tweak to `cata`

, we can get `para`

:

```
para :: (Fixable t (t, z) -> z) -> t -> z
= teardown
para alg where
= alg
teardown . fmap (\t -> (t, teardown t))
. toFixable
```

## Miscellaneous Findings

### All Injective Functions are Catamorphisms

Meijer et al. make the somewhat-unsubstantiated claim that all injective functions are catamorphisms. We will reproduce their proof here, and then work through it to convince ourselves of its correctness.

Let

`f :: A -> B`

be a strict function with left-inverse`g`

. Then for any`φ :: F A -> A`

, we have:`. f = id g . cata φ = cata (f . φ . fmap g) f`

Taking `φ = fromFixable$ we immediately get that any strict injective function can be written as a catamorphism:

`= cata (f . fromFixable . fmap g) f`

Sounds, good? I guess? Meijer et al. must think I’m very smart, because it took me about a week of bashing my head against this proof before I got it. There were two stumbling blocks for me which we’ll tackle together.

To jog our memories, we’ll look again at the definition of `cata`

:

`= φ . fmap (cata φ) . toFixable cata φ `

There are two claims we need to tackle here, the first of which is that given `φ = fromFixable`

:

`. cata φ = cata (f . φ . fmap g) f `

We can show this by mathematical induction. We’ll first prove the base case, by analysis of the `[]`

case over list-algebras.

```
. φ . fmap g) []
cata (f -- definition of cata
= f . φ . fmap g . fmap (cata (f . φ . fmap g)) $ toFixable []
-- definition of toFixable
= f . φ . fmap g . fmap (cata (f . φ . fmap g)) $ NilF
-- fmap fusion
= f . φ . fmap (g . cata (f . φ . fmap g)) $ NilF
-- NilF is a constant functor
= f . φ $ NilF
-- substitute φ = fromFixable
= f $ fromFixable NilF
-- definition of fromFixable
= f []
```

Great! That’s the base case tackled. It’s easy to see why this generalizes away from lists to any data structure; the only way to terminate the recursion of a `cata`

is for one of the type’s data constructors to not be recursive (such as `Nil`

). If the data constructor isn’t recursive, its `Fixable`

representation must be a constant functor, and thus the final `fmap`

will always fizzle itself out.

Let’s tackle the inductive case now. We’ll look at cases of `cata`

that don’t fizzle out immediately:

```
. φ . fmap g)
cata (f -- definition of cata
= f . φ . fmap g . fmap (cata (f . φ . fmap g)) . toFixable
-- fmap fusion
= f . φ . fmap (g . cata (f . φ . fmap g)) . toFixable
-- definition of cata
= f . φ . fmap (g . f . φ . fmap g . fmap (cata (f . φ . fmap g)) . toFixable) . toFixable
-- fmap fusion
= f . φ . fmap (g . f . φ . fmap (g . cata (f . φ . fmap g)) . toFixable) . toFixable
-- g . f = id
= f . φ . fmap (id . φ . fmap (g . cata (f . φ . fmap g)) . toFixable) . toFixable
-- definition of id
= f . φ . fmap (φ . fmap (g . cata (f . φ . fmap g)) . toFixable) . toFixable
```

As you can see here, subsequent expansions of `cata`

line their `g`

s and `f`

s up in such a way that they cancel out. Also, we know from our experience looking at the base case that the final `g`

will always sizzle out, and so we don’t need to worry about it only being a left-inverse.

The other stumbling block for me was that `cata fromFixable = id`

, but this turns out to be trivial:

```
cata fromFixable= fromFixable . fmap (cata fromFixable) . toFixable
```

Eventually this will all bottom out when it hits the constant functor, which will give us a giant chain of `fromFixable . toFixable`

s, which is obviously `id`

.

To circle back to our original claim that all injective functions are catamorphisms, we’re now ready to tackle it for real.

```
. cata φ = cata (f . φ . fmap g)
f . cata fromFixable = cata (f . fromFixable . fmap g)
f . id = cata (f . fromFixable . fmap g)
f = cata (f . fromFixable . fmap g) f
```

\(\blacksquare\)

### All Surjective Functions are Anamorphisms

Anamorphisms are dual to catamorphisms, and surjective functions are dual (in \(\mathbb{Set}\)) to injective functions. Therefore, we can get this proof via duality from the proof that injective functions are catamorphisms. \(\blacksquare\)

## Closing Remarks

*Functional Programming with Recursion Schemes* has some other (in my opinion) minor contributions about this stuff, such as how catamorphisms preserve strictness, but I feel like we’ve tackled the most interesting pieces of it. It is my hope that this review will serve as a useful complement in understanding the original paper.